HoLEP vs TURP in Benign Prostatic Hyperplasia: A Systematic Review - Krista, Kevin Aldenio Hatma; Budiono, Nur (Penerbit Goodwood, 2026)
Purpose: This review evaluates the efficacy, safety, and durability of HoLEP versus TURP, addressing the research gap concerning their comparative long-term stability and performance across varying prostate volumes. The study focuses on functional outcomes, complication profiles, and the scalability of each technique. Research Methodology: A systematic search (2020–2025) identified RCTs and meta-analyses comparing HoLEP and TURP in BPH patients. Parameters analyzed included IPSS, Qmax, PVR, perioperative outcomes, and reoperation rates. Results: Both procedures show comparable functional gains. However, HoLEP offers a superior perioperative profile, significantly lower bleeding risk, and higher long-term durability. Furthermore, HoLEP’s efficacy is independent of prostate size, whereas TURP efficiency diminishes in larger glands. Conclusions: Despite a steeper learning curve, HoLEP’s safety and versatility position it as the primary modern surgical standard. TURP remains a relevant alternative depending on institutional facilities. Conclusions: Despite having a longer learning curve, HoLEP is worthy of consideration as the primary choice in modern surgical management of BPH, while TURP remains relevant in certain conditions and facilities. Limitations: Limitations of this systematic review are the heterogeneity of study designs, populations, and follow-up durations, which may affect the comparability of results. Contributions: This review provides a contemporary evidence-based guide for clinicians in selecting optimal surgical interventions.